Early marriage and teenage pregnancy: The unspoken consequences of COVID-19 pandemic in Nigeria - Shuaibu Saidu Musa; Goodness Ogeyi Odey; Muhammad Kabir Musa; Samar Mohammed Alhaj; Blessing Abai Sunday; Suleiman Maimuna Muhammad; Don Eliseo Lucero- Prisno (Elsevier, 2021)
Early marriage and its sad consequences to the girl child and socio-economic development of the nation has been an age-long issue being advocated against in many parts of Nigeria. At the onset of COVID-19, the teeming efforts to curb this issue almost got jeopardized with harsh economic situations in many households due to the lockdown and the willingness to marry off their girls to reduce this burden. Closure of schools and cases of sexual gender based violence also impacted the prevalence of early marriage during the pandemic in Nigeria. We also argue in this commentary that the pandemic has so much impacted on programs aimed at ending early marriage in the nation. Therefore, if serious and concerted efforts are not taken by relevant stakeholders, more girls will be at risk of early marriage and teenage pregnancy with their related health consequences. They will also be left behind in fulfilling their potentials and their aspirations cut off with early marriage, thus sustainable development cannot be achieved.